Effect of symmetry center losses on energy bands and carrier kinematics in Zn₃As₂ and Cd₃As₂ - Chuiko, G.; Don, N.; Martyniuk, V.; Stepanchikov, D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
The comparative analysis of the band structure and carrier kinematics for Zn₃As₂ and Cd₃As₂ has been executed. The influence of presence and absence of symmetry center in different crystalline phases of the above materials is explored. The direct and indirect solutions of dispersion equations were used for the analysis. The results of researches are presented in the form of graphic dependences. The splitting of energy bands caused by the symmetry center loss is estimated. Such splitting is maximal along any directions normal to the main crystalline axis. The principle possibility of the carrier separation by spin with the use of found distinction for the modules of their velocities is shown.